Trade and Political Relations Between the Czech Republic and Latin American Countries - Rýcová, Zuzana; Urban, Traian; Kadeřábková, Jaroslava, 1942-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
Main objective of the thesis is to evaluate trade and political relations between the Czech Republic and selected countries in Latin America (selected countries will be those with strongest ties to the Czech Republic). Hypothesis: Trade and political relations between Czech Republic and Latin American Countries are well developing in the course of the time. Latin-American region provides a great potential for future cooperation. Emphasis will be targeted on the assessment of business conditions (including bilateral agreements on mutual trade), further on the most important export commodities and investment opportunities. At the same time, the work will attempt to estimate the level of potential of Latin American territory and further direction of mutual relationships. The research will contain a questionnaire for Czech entrepreneurs operating in Latin America and a thorough analysis of mutual trade will be given. Unfortunately, this subject is not documented with a large number of printed books, therefore, the key source of information will be databases and statistical information published by state institutions (Chamber of Deputies, Ministry of Foreign Affairs, Ministry of Industry and Trade, etc.). Bibliography: [1] AGUIAR DE MEDEIROS, C. (2011): The Political Economy of Institutional Change and Economic Development in Latin American Economies. Journal of Economic Issues, Vol. XLV, No. 2 (June 2011), DOI: 10.2753/JEI0021-3624450205, pg. 289 - 299 [2] Chairman of the Chamber of Deputies of the Parliament of the Czech Republic: Report on Relationships between the Czech Republic and Latin American Countries and the Role of the Chamber of Deputies in this Process (2010). [3] CHRISTIAN, S. (1997): Latin American Trade Relations. Journal of Interamerican Studies and World Affairs, Vol. 39, No. 1, Special Issue: US-Latin American Relations (Spring, 1997), pp. 71 - 83 [4] GÓMEZ-MERA, L. -- BARRETT, B.
(2012): The Political Economic of Preferential Trade Agreements: Latin America and Beyond. DOI: 10.1111/j.1548-2456.2012.00147.x. Available at: http://miami.academia.edu/LauraGomezmera/Papers/35945 /The_Political_Economy_of_Preferential_Trade_Agreements_Latin_America_and_Beyond [5] GRINBERG, N. (2010): Where Is Latin American Going? FTAA or "Twenty-first-Century Socialism"?. Latin American Perspective 2010. DOI: 10.1177/0094582X09351713, pg. 185 - 202 [6] SHADLEN, K.C. (2006): Latin American Trade and Development in the New International Economy. Latin American Research Review, Vol. 41, No.3 (2006), pg. 210 - 267
Vedoucí práce: Traian Urban
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses